Elevated serum chromogranin A levels are independently associated with metabolic and inflammatory disturbances in polycystic ovary syndrome - Alarslan, Pınar; Doruk, Mehmet (Frontiers in Endocrinology, 2025)
IntroductionPolycystic ovary syndrome (PCOS) is a multifactorial endocrine disorder characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology, frequently accompanied by insulin resistance, inflammation, and other metabolic disturbances. Chromogranin A (CgA), a glycoprotein secreted by neuroendocrine cells, has been linked to metabolic regulation and inflammatory processes, but its role in PCOS remains unexplored. This study aimed to evaluate serum CgA levels in women with PCOS and their association with metabolic, hormonal, and inflammatory parameters.MethodsThis case-control study included 75 women with PCOS, diagnosed according to the Rotterdam criteria, and 75 age-matched healthy controls, recruited between January and April 2021 at Istanbul Aydın University Medical Park Florya Hospital. Serum CgA levels were measured using ELISA. Clinical parameters and biochemical markers, including glucose, insulin, HOMA-IR, lipid profile, sex hormones, SHBG, and hs-CRP, were assessed. Correlation, multivariate linear regression.ResultsMean serum CgA levels were significantly higher in the PCOS group than in controls (934.68 ± 256.27 vs. 642.27 ± 197.63 pg/mL, p < 0.001). PCOS patients also had higher glucose, insulin, HOMA-IR, triglycerides, hs-CRP, LH, total testosterone, FAI, and DHEA-S, with lower HDL-C and SHBG (all p < 0.05). CgA correlated positively with BMI, glucose, insulin, HOMA-IR, and hs-CRP, and remained independently associated with BMI, HOMA-IR, and hs-CRP in multivariate analysis. In multivariable models, CgA remained independently associated with BMI, HOMA-IR, and hs-CRP. These findings suggest that CgA reflects the metabolic–inflammatory milieu accompanying PCOS rather than indicating PCOS per se.DiscussionElevated CgA levels in PCOS are independently associated with obesity, insulin resistance, and low-grade inflammation. CgA may serve as a novel biomarker for metabolic risk stratification in PCOS, warranting validation in larger, prospective studies.